Studi Korelasi Program Pelatihan Tatarias Kecantikan dengan Sikap Wirausaha Warga Belajar di Lembaga Pendidikan Nonformal - Ida Rosita; M A Rizka (Jurnal Paedagogy, 2021)
This study aims to analyze the correlation between the bridal make-up training program and the entrepreneurial attitude of students at the non-formal education institution of LKP Kartika. This study uses a correlational method with a quantitative approach. This research is a population study with 12 trainees as respondents. Data collection techniques using questionnaires and documentation. The data analysis method used is product moment correlation analysis. The results of the rxy calculation obtained in this study are 0.619, while the value of r Product Moment in the table with a significance level of 5% and N = 12 is 0.576. So that the calculated r value is greater than the Product Moment r value in the table (0.619 > 0.576) with the conclusion that there is a relationship between the bridal make-up training program and the entrepreneurial attitude of citizens studying at non-formal education institutions LKP Kartika.